Distressed debt-investing in Deutschland: Geschäftsmodelle und Perspektiven - Christoph Schalast; Christian Daynes (HfB - Business School of Finance & Management, 2005)
The global distressed debt market has been established for some years now, however within this investment universe German Distressed Debt is generally considered as underdeveloped. The aim of this paper is to highlight why Investments are transacted and the framework of processes involved within the German market additionally; the paper focuses on current active investors and concludes with a market survey covering the impressions of these participants.
urn:nbn:de:101:1-20080825178
Keywords: K12; K19; K22; K29; 330; Non-Performing-Loans; Distressed Debt; Distressed Debt-Trading; Bad Bank; Work-Out; Outsourcing; Data Protection; Bankers duty of secrecy; Due Diligence; Kreditrisiko; Kreditmarkt; Geschäftsmodell; Deutschland